β-Transducin Repeat-containing Protein 1 (β-TrCP1)-mediated Silencing Mediator of Retinoic Acid and Thyroid Hormone Receptor (SMRT) Protein Degradation Promotes Tumor Necrosis Factor α (TNFα)-induced Inflammatory Gene Expression - Hsu, Kuo-Sheng (American Society for Biochemistry and Molecular Biology, 2013)
Cytokine modulation of the endothelium is considered an important contributor to the inflammation response. TNFα is an early response gene during the initiation of inflammation. However, the detailed mechanism by which TNFα induces proinflammatory gene expression is not completely understood. In this report, we demonstrate that silencing mediator of retinoic acid and thyroid hormone receptor (SMRT) represses the expression of a subset of TNFα target genes in human umbilical vein endothelial cells. Upon TNFα stimulation, we observed an increase in the E3 ubiquitin ligase β-TrCP1 and a decrease in SMRT protein levels. We show that β-TrCP1 interacts with SMRT in a phosphorylation-independent manner and cooperates with the E2 ubiquitin-conjugating enzyme E2D2 to promote ubiquitination-dependent SMRT degradation. Knockdown of β-TrCP1 increases SMRT protein accumulation, increases SMRT association with its targeted promoters, and decreases SMRT target gene expression. Taken together, our results support a model in which TNFα-induced β-TrCP1 accumulation promotes SMRT degradation and the subsequent induction of proinflammatory gene expression.